Des chevaux précepteurs de mineurs ; des conditions aux cas (France, XIXe-XXe siècles) - Baratay, Éric (Anthropologica, 2020)
In the restricted, constrained, and dangerous world of the mines, where habituation and adaptation are essential for survival and expression, veterinarians, engineers, and miners have observed and documented the knowledge and skills gradually acquired by horses as well as the initiatives taken by them. Horses have been found to adapt to situations, to anticipate changes, and to make the best possible decisions, to the point where some men have not hesitated to take inspiration from their animal partners, to delegate initiatives to them and even to confide in them, to let themselves be “taught” some attitudes or to imitate others. This habituated, experienced, autonomous, and pedagogical state of being-horse is possible and achievable only if the horse has mastered demanding work and adapted to harsh conditions, and if it is blessed with an adequate individual character and an attentive, reassuring, conciliatory human companionship, all of which allows it to overcome the multiple situations of stress and fatigue that generate depression and resistance, but also the refusal to work and reforms.